Vocational education and training reform in India : business needs in India and lessons to be learned from Germany. Working paper - Mehrotra, Santosh [Verfasser]; Raman, Ravi [Verfasser]; Kumra, Neha [Verfasser]; Kalaiyarasan [Verfasser]; Röß, Daniela [Verfasser] (Bertelsmann Stiftung, 2014)
"India is among the countries with the lowest proportion of trained youth in the world. Moreover, Vocational Education carried out in secondary schools (since the mid-1980s) has received very limited funding in recent times; it has remained non-aspirational, of poor quality and involves little industry collaboration. In contrast, the Vocational Education and Training (VET) system in Germany is characterized by much higher proportion of youth participation, intensity of private sector participation and a basis in legislation. In this context, this study seeks to understand the experience of Germany's Dual System of education and training as it has been historically cited as a successful model. The study involved a primary survey of 44 firms, mostly large, all in the organized sector, and most in manufacturing. It attempted to identify the skills gaps experienced by German, Indian and joint-venture firms in India. The study asserts the need to restructure and re-orient the Indian Technical Vocational Education and Training (TVET) system to address current and prospective challenges by taking on board major social partners: the corporate sector, the state and students/parents." (Hrsg.; BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.3.4 Asien; I 1.1 Systemberatung; Berufsbildung; Berufsbildungssystem; Qualifikationsbedarf; Fachkräftequalifizierung; Duales System; Bildungsexport; Indien; Bundesrepublik Deutschland